ETHNIC VIOLENCE AND TERRORISM AS INTERNAL CHALLENGES TO CHINA'S NATIONAL SECURITY: A CASE STUDY OF XINJIANG - Trailović, Dragan (The Policy of National Security, 2023)
The national security of the People’s Republic of China is susceptible to an array of intricate internal challenges, risks and threats. This includes challenges that may be of a political nature, risks caused by economic and social differences, threats caused by tensions in ethnic relations, as well as many others. This paper seeks to concentrate on ethnic tensions, namely ethnic violence and terrorism, as the most substantial factors that pose a significant threat to the country’s stability and security. The paper delves into the development of ethnic tensions and conflicts resulting from the interaction between Chinese authorities and factions within the Uyghur movement for national self-determination. It emphasizes the extremist current within the broader Uyghur ethnonational movement that utilizes violence and acts of terrorism in political activism. This paper aims to follow the evolution and changes of strategies and tactics employed by Uyghur nationalists in Xinjiang over time and present the most characteristic violent and terrorist incidents that occurred in Xinjiang to exemplify these alterations. These changes are reflected in increased violence, a shift in targets from primarily security forces to civilians, including violent clashes between Uyghur and Han citizens and an expansion in the geographic reach of attacks.
Keywords: national security; People’s Republic of China; Xinjiang (XUAR); East Turkistan; Uyghur issue; ethnic violence; terrorism